Impact of the Global Financial Crisis on GCC- UAE's Banking Sector - Jaber, Hoda (2012)
The rationale behind this paper is to inspect the impact of the global financial crisis on GCC countries, UAE in particular & its banking sector. To assess the extent of that effect, this paper provides some comparison before & after the crises. Additionally, it examines the challenges & recommendations. Whilst for various GCC the effects of the crisis have been considered to be mild compared to the rest of the world, its impact had been ruthless in some countries, including UAE. A lot of GCC countries have made an gigantic effort in strengthening their policy frameworks and sturdiness, thought-provoking a healthy economic growth, improving the sovereign wealth fund, foreign reserve, financial systems, and the account balance. But a lot are still considered being highly susceptible to a deep global downturn that is so very well linked to oil prices. This paper provides policy advice on how best to address the impact of the crisis on GCC countries, UAE banking sector specifically, and describes suitable measures & policies that should be adopted. It is crucial to set up managed financing facilities to help out sms's, the real-estate sector, the bank operations and industrial sectors, while making efforts to maintain and catalyze additional